The Turkish economy: A winner of the Euro crisis? - Secil Pacaci Elitok; Thomas Straubhaar (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
While Turkey has opened up for trade, and export orientation has been seen as an important tool for development, foreign direct investments (FDI) have lagged behind. Turkey has not attracted a lot of FDI. Less than one billion US- FDI came to Turkey per year before 2000. In the last decade, FDI to Turkey has risen sharply to a peak of about 22 billion US- in 2007 but with a significant decrease since (as a consequence of the worldwide international financial crisis).
Keywords: 330